Tribochemistry of phenol and benzyl alcohol between YG8 self‐mated interfaces. (24th October 2022) - Zhang, Renhui; Zhang, Qiao; Luo, Yuzhou; Wu, Ruolin; Li, Longcheng
Abstract : In this work, the tribological performance of mixed lubricant consisting of phenol and benzyl alcohol between YG8 self‐mated interfaces was systematically investigated under 98 N and 1450 rpm. The results showed that with increasing concentration of phenol in the mixed lubricant, the friction coefficient initially decreases and then increases; however, anti‐wear performance initially was enhanced and then weaken. As the concentration of phenol was 1.0 wt.%, the tribo‐system exhibited the lowest friction coefficient and wear scar diameter. TEM, SEM and XPS techniques were employed to probe the possible tribological mechanism sliding in the mixed lubricant containing 1.0 wt.% of phenol. The phenol effectively slowed down the oxidation of the mixed lubricant, combination of friction‐induced tungsten oxides and carbon quantum dots, assuring the tribo‐system still in mixed lubrication condition, which made the tribo‐system maintain low friction coefficient and wear.